2018
DOI: 10.1002/psp.2154
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dispersion of U.S. national origin groups: Characteristics of dispersed immigrants and settlement places

Abstract: This article examines the individual and economic context correlates of foreign‐born dispersion in the 2007–2011 period using confidential American Community Surveys and census data. For 40 national origin groups and other foreigners from 7 world regions, group‐specific settlement indicators for 741 geographic areas were used to estimate dispersion relationships to human capital, acculturation, settlement region, and economic context. A fixed‐effect model estimated with individual indicators, net of national o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The greater propensity of foreigners to migrate is the main shared result (Finney & Catney, 2012 ;Silvestre & Reher, 2014 ). While the results of studies on migration distance for foreigners in comparison to that of nationals are controversial (Casacchia et al, 2019 ;Sapiro, 2017 ) some researchers have identified remarkable differences among the internal migration patterns of ethnic groups (Kritz & Gurak, 2018 ;Sapiro, 2017 ;Trevena et al, 2013 ). Different levels of migration -and of the distance migrated -have also been observed in diverse ethnic groups (Finney & Simpson, 2008 ).…”
Section: Theore Tic Al Fr Ame Work and Re S E Arch Hyp Othe S E Smentioning
confidence: 99%
“…The greater propensity of foreigners to migrate is the main shared result (Finney & Catney, 2012 ;Silvestre & Reher, 2014 ). While the results of studies on migration distance for foreigners in comparison to that of nationals are controversial (Casacchia et al, 2019 ;Sapiro, 2017 ) some researchers have identified remarkable differences among the internal migration patterns of ethnic groups (Kritz & Gurak, 2018 ;Sapiro, 2017 ;Trevena et al, 2013 ). Different levels of migration -and of the distance migrated -have also been observed in diverse ethnic groups (Finney & Simpson, 2008 ).…”
Section: Theore Tic Al Fr Ame Work and Re S E Arch Hyp Othe S E Smentioning
confidence: 99%